2012
DOI: 10.1038/bmt.2012.177
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of 25-hydroxyvitamin D before allogeneic hematopoietic SCT correlate with the development of chronic GVHD

Abstract: Vitamin D, a hormone involved in bone and calcium homeostasis, has been shown to have potent immunomodulatory effects. We performed a retrospective cohort analysis to evaluate whether monohydroxyvitamin D levels before allogeneic hematopoietic SCT (HSCT) correlate with the risk of GVHD. Fifty-three patients who underwent myeloablative HSCT were studied. Vitamin D levels were measured in serum samples obtained before HSCT. The median 25-hydroxyvitamin vitamin D level was 21.9 ng/mL (7.8-45.7). The cumulative in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
3
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(77 citation statements)
references
References 50 publications
7
61
3
4
Order By: Relevance
“…This might be because IDO activity in serum by circulating monocytes 26 overshadows DC activity in the tissues, but more studies focusing on vitamin D effects in vivo are needed. Previous studies have shown conflicting results; although one study on 53 adult patients suggests an association between vitamin D levels and cGvHD incidence, 6 others have reported better outcomes in established cGvHD after vitamin D supplementation. 27 A recent study on 123 pediatric patients failed to show an association between pre-transplantation vitamin D levels and cGvHD incidence.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This might be because IDO activity in serum by circulating monocytes 26 overshadows DC activity in the tissues, but more studies focusing on vitamin D effects in vivo are needed. Previous studies have shown conflicting results; although one study on 53 adult patients suggests an association between vitamin D levels and cGvHD incidence, 6 others have reported better outcomes in established cGvHD after vitamin D supplementation. 27 A recent study on 123 pediatric patients failed to show an association between pre-transplantation vitamin D levels and cGvHD incidence.…”
Section: Discussionmentioning
confidence: 77%
“…[2][3][4] A vitamin D-enriched milieu maintains an immature DC phenotype associated with decreased ability to stimulate alloreactive T cells in MLCs. 5 Vitamin D deficiency has been associated with an increased incidence of chronic GvHD, 6 and supplementation with vitamin D to induce a tolerogenic DC population has been suggested for prevention of GvHD. 7 One mechanism for this maintenance of an immature DC population has been shown to be the upregulation of indoleamine 2,3-dioxygenase (IDO), 8 an enzyme converting tryptophan to kynurenine and a central feature in tolerizing DCs.…”
Section: Introductionmentioning
confidence: 99%
“…Este alto porcentaje es concordante con la literatura internacional que muestra una frecuencia de insuficiencia de vitamina D entre 70 y 100% en pacientes sometidos a TPH 7,16,17 . Este hecho es de especial relevancia clínica considerando que, como ya fue mencionado, datos recientemente publicados muestran que el déficit de vitamina D puede impactar negativamente en la respuesta a tratamiento, así como en la sobrevida en algunas neoplasias hematológicas [8][9][10][11][12] . Encontramos también una alta frecuencia de hiperparatiroidismo secundario que en parte puede ser explicado por el déficit de vitamina D, pero deben considerarse otros factores tales como alteraciones de absorción intestinal de calcio, alteraciones de hidroxilación renal de la vitamina D, procesos inflamatorios sistémicos, entre otros.…”
Section: Discussionunclassified
“…Concordante a lo anterior Wallace et al encontró que el déficit de Vitamina D (< 20 ng/mL) 100 días post TPH en niños se asociaba a disminución significativa en la sobrevida global 10 . Glotzbecker et al demostró en pacientes evaluados pre TPH alogénico, que aquellos con déficit de vitamina D (< 25 ng/mL) tenían incidencia acumulada de GVHD crónico a dos años significativamente mayor que aquellos con niveles sobre 25 ng/mL 11 . Por último con respecto a Vitamina D y neoplasias hematológicas Kelly et al reportó una asociación inversa entre el riesgo de Linfoma no Hodgkin y el tiempo de exposición solar en pacientes de 13 a 21 años, presuntamente mediada por cambios en el metabolismo de vitamina D y su receptor 12 .…”
unclassified
“…Patients who are at increased risk of infection, such as those undergoing chemotherapy or with altered immune function (such as transplant patients), might benefit from rapid normalization of vitamin D status. 29,30 These clinical benefits are hypothetical at present but can be tested using this supplementation method.…”
Section: Discussionmentioning
confidence: 99%